New cytochalasan alkaloids and cyclobutane dimer from an endophytic fungus Cytospora chrysosperma in Hippophae rhamnoides and their antimicrobial activities. (21st December 2021) - Mou, Qing-Lin; Yang, Sheng-Xiang; Xiang, Ting; Liu, Wen-Wen; Yang, Jian; Guo, Lan-Ping; Wang, Wen-Jing; Yang, Xiao-Long
Graphical abstract: Highlights: The secondary metabolites of Cytospora chrysosperma were firstly investigated. Three new cytochalasans and a new cyclobutane dimer were isolated and determined. Cytochrysins A and C showed significant antibacterial activity. Abstract: Three new cytochalasan alkaloids, cytochrysins A-C (1 –3 ), and a new cyclobutane dimer, cytospodimer A (4 ), along with three known compounds (5 –7 ), were isolated from the solid culture of Cytospora chrysosperma, an endophytic fungus isolated from Hippophae rhamnoides . Their structures were determined by a combination of spectroscopy and single-crystal X-ray crystallography. Compound 1 showed significant antibacterial activity against multi-drug resistant Enterococcus faecium with an MIC value of 25 μg/mL, and compound 3 against methicillin-resistant Staphylococcus aureus with an MIC value of 25 μg/mL.